Analysis of Corruption-Free Area Indicators in the Government of Gorontalo Province - Biahimo, Jurni; Mustapa Wantu, Sastro; Aneta, Yanti; Sulila, Ismet (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This study aims to analyze the implementation of the Integrity Zone in creating a clean and corruption-free bureaucracy in the Gorontalo Provincial Government. This study uses a qualitative approach with a case study method, which involves in-depth interviews, observations, and document analysis related to the policies and implementation of the Integrity Zone program in various local government agencies. The results of the study show that the implementation has experienced significant developments, especially in terms of increasing transparency of public services and strengthening the internal monitoring system. However, there are still several obstacles faced, such as the low understanding of employees regarding the concept of integrity in bureaucracy and resistance to change, especially in the implementation of digitalization of administrative servicesTherefore, a more comprehensive strategy is needed to increase the effectiveness of this program, such as optimizing information technology, strengthening internal supervision, and providing incentives for work units that successfully implement the integrity principle optimally. With these steps, it is hoped that the Integrity Zone can become the main instrument in creating cleaner, more transparent, and more accountable governance in Gorontalo Province.